The effect of a neuromuscular vs. dynamic warm-up on physical performance in young tennis players - Fernandez-Fernandez, J.; Garcia-Tormo, V.; Santos-Rosa, F. J.; Teixeira, A. S.; Nakamura, F. Y.; Granacher, U.; Sanz-Rivas, D. (The Journal of Strength and Conditioning Research, 2020)
The aim of this study was to examine performance-enhancing (i.e., training) effects of a neuromuscular warm-up (NWU) compared with a dynamic WU (DWU) in young tennis players. Twenty-eight well-trained male tennis players with a mean age of 15.09 ± 1.16 years participated in this study and were assigned to either a training group performing NWU (n = 14), or a group that followed DWU (n = 15) before tennis-specific training, for 8 weeks. Pretest and posttest included: speed (5, 10, and 20 m); modified 5-0-5 change of direction (COD) test; bilateral/unilateral countermovement jump (CMJ); 2 kg overhead, forehand, and backhand-side medicine ball throw performance (MBT); serve velocity, and shoulder strength and range-of-motion (ROM) performance (i.e., internal [IR]/external [ER] rotation). Results showed that both groups, NWU and DWU, significantly improved their sprint performances (5-20 m; [p < 0.05; d = 0.83-1.32]), CMJ (bilateral and unilateral [dominant side] [p < 0.005; d = 1.27-1.59]), overhead MBT (p = 0.014; d = 1.02), and some shoulder strength (i.e., IR dominant side [D], ER D, ER/IR ratio [p < 0.05; d = 0.86-1.59]) and ROM (i.e., ER D, total ROM D [p < 0.05; d = 0.80-1.02]) values. However, the interaction effects revealed that NWU compared with DWU produced greater performance gains in most of the analyzed parameters (i.e., 5-10 m sprint, CMJ, overhead MBT, serve speed). The inclusion of an NWU characterized by a relatively low volume (~20-35 minutes), including general mobility, core, and shoulder strength exercises, combined with neuromuscular-related exercises (e.g., plyometric and acceleration/deceleration/COD drills), can be recommended to obtain positive effects in tennis performance-related variables.